Predictors of in-hospital Mortality After Rapid Response System Activation in a Newly Established Tertiary Hospital - Büşra Tezcan; Müçteba Can; Çilem Bayındır Dicle; İbrahim Mungan; Derya Ademoğlu (Galenos Yayinevi, 2022)
Objective:Rapid response systems (RRSs), which aim to prevent cardiac arrests and unexpected deaths, have been implemented across hospitals worldwide. Most studies on RRS shave evaluated the effects of its implementation on in-hospital mortality. In this study, we evaluated the predictive factors of in-hospital mortality for patients who were subjects of RRS activation in a newly established major hospital in Turkey.Materials and Methods:Data on RRS activations were reviewed from paper charts and electronic medical records between March 2019 and February 2020. The demographic characteristics of patients, time of and reasons for RRS activation, initial cardiac rhythm, heart rate, mean arterial pressure, pulse oximetry-measured blood oxygen saturation (SpO2), time of arrival of the rapid response team, red cell distribution width, platelet distribution width obtained from the first blood gas analysis and haemogram test results as well as glucose, sodium, potassium, pH, lactate, neutrophils and lymphocyte levelswere recorded. Univariate and multivariate logistic regression analyses were conducted to determine the independent predictors of in-hospital mortality.Results:A total of 531 patients were included in the analysis. Of these, 189 (35.6%) died during hospital admission. Compared with survivors, non-survivors were older (median age, 64 vs. 52 years) and more likely to be male (65.6% vs. 34.4%); be admitted for cardiovascular, pulmonary and oncologic diseases and trigger RRS at nightand weekends than during the day. Activation of RRS by respiratory and haemodynamic triggers as well as during nighttime and weekend hours oncologic reasons for hospital admission, low SpO2 levels, high neutrophil-to-lymphocyte ratio (NLR), potassium levels and lactate levels were predictive of in-hospital mortality.Conclusion:This study found some weaknesses in the current RRS of the hospital. Hospital staffs working overnight and on weekends should be trained and empowered. SpO2, potassium and lactate levels as well as NLR are predictors of in-hospital mortality and can guide triage decision making, which is usually a challenging and stressful task.